IMPLEMENTATION OF TGT LEARNING MODEL TO IMPROVE LEARNING ACTIVITIES AND STUDY RESULTS - Widodo, Sulistyo (JCER (Journal of Chemistry Education Research), 2018)
Abstract. This Classroom Action Research (CAR) aimed to know how the implementation of TGT Learning Model can improve the learning activities and study results of the students of class X MIPA H. SMAN 1 Kediri, This students learning activities at the first cycle was 46.8 % and the second cycle was 69.28 %, The study results at the first cycle was 33.33 % and the second cycle was 83.33 %. It can be concluded that TGT Learning Model can improve the learning activities and study results.